Kritik Feminisme Pada Web Series “Gadis Kretek” - Jaya, Eko Pebryan; Yogsunandar, Harry (Jurnal Publisitas, 2024)
Technological developments and transformations in the entertainment industry have brought about major changes in the way we access and consume films. Currently, films are not only available in cinemas, but have also spread through online streaming services. Various series with various story themes appeared, one of which was "Gadis Kretek". This series not only shows a romantic drama set in the development of the kretek industry in two different time periods, but also deals with issues surrounding women. Basically, media products have meaning through the signs in their messages. This research uses a descriptive qualitative approach, using John Fiske's semiotic analysis method, feminist criticism focuses on portraits of women in the context constructed by web series creators, where female characters are depicted as empowered subjects or simply as objects trapped in patriarchal stereotypes. The research results show that the "Gadis Kretek" series is a complex medium for understanding the dynamics of women in society, as well as providing space for feminist criticism of gender norms constructed by the director.